Evaluation of sericin as a fetal bovine serum-replacing cryoprotectant during freezing of human mesenchymal stromal cells and human osteoblast-like cells - Verdanova, Martina; Pytlik, Robert; Kalbacova, Marie Hubalek (Biopreservation and biobanking, 2014)
A reliable, cryoprotective, xeno-free medium suitable for different cell types is highly desirable in regenerative medicine. There is danger of infection or allergic reaction with the use of fetal bovine serum (FBS), making it problematic for medical applications. The aim of the present study was to develop an FBS-free cryoprotective medium for human mesenchymal stromal cells (hMSCs; primary cells) and immortalized human osteoblasts (SAOS-2 cell line). Furthermore, we endeavored to eliminate or reduce the presence of dimethyl sulfoxide (DMSO) in the medium. Sericin, a sticky protein derived from the silkworm cocoon, was investigated as a substitute for FBS and DMSO in the freezing medium. Cell viability (24 hours after thawing, both hMSC and SAOS-2) and colony-forming ability (2 weeks after thawing, only for hMSCs) were both determined. The FBS-free medium with 1% sericin in 10% DMSO was found to be a suitable freezing medium for primary hMSCs, in contrast to immortalized human osteoblasts. Surprisingly, the storage of hMSCs in a cultivation medium with only 10% DMSO also provided satisfactory results. Any drop in DMSO concentration led to significantly worse survival of cells, with little improvement in hMSC survival in the presence of sericin. Thus, sericin may substitute for FBS in the freezing medium for primary hMSCs, but cannot substitute for DMSO.
Keywords: sérum; Freezing; sericiny; Osteoblasts; kryoprezervace; Cryopreservation; Cryoprotective Agents; Mesenchymal Stem Cells; skot; Serum; Dimethyl Sulfoxide; Culture Media, Serum-Free; mezenchymální kmenové buňky; osteoblasty; dimethylsulfoxid; zvířata; Humans; Cattle; Cell Survival; viabilita buněk; kultivační média bez séra; zmrazování; kryoprotektivní látky; Sericins; lidé; Animals